Using 'Homemade' Documentary Video in Religious Studies - Alexander, Scott C. (The journal of religion and film, 1997)
On the whole, the lesson I learned from making Abraham's Children, and the one I would like to pass on, is a fairly simple one. If an instructor can imagine a video that would enhance his or her religious studies teaching in specific ways, but cannot seem to find a strong candidate available in the current market, that instructor may want to consider producing a "homemade" video with the primary goal of improving his or her own students' education, and the secondary aim of making your project available for purchase to colleagues who may be facing similar pedagogical challenges. In our current higher educational climate, in which there appears to be much interest in and funding for improving undergraduate instruction through the application of new media technologies, those of us who teach religion and who think we have ideas for quality instructional films, might well want to strike while the iron's hot, and see if there is not some way we can create these films ourselves. I speak from experience when I say that the process can be an extremely rewarding one.